PEMAHAMAN ANGGOTA KELOMPOK TENTANG ASAS KERAHASIAAN DALAM LAYANAN KONSELING KELOMPOK DI SMAN 14 PADANG - Jamal, Ilhamda (Bimbingan dan Konseling, 2014)
The background of this study, by the members of the group who presence did not understand the principle of confidentiality, considers the principle of confidentiality rules and not merely to understand the impact on group counseling. The purpose of the study described: 1) an understanding of the meaning is the principle members of a group of confidentiality in counseling group services. 2) understanding of the principles of group members about the impact of confidentiality for group members. This type of research is descriptive. The population learners Public High Schools 14 Padang the group ever counseling services totaling 32 people, with a sampling technique is saturated samples. Source of data is the primary data and secondary data. The research instrument is a questionnaire, analysis using the criterion formula Sturgess. Results of the study revealed: 1) an understanding principles of the group members in order content section principle of confidentiality category quite well. 2) understanding of the principles group members about the impact confidentiality for members of the group: a) the positive impact category is quite well. b) the negative impact category is quite well.